Age‐specific influences of emotional distress on performance status in cancer patients. Issue 10 (25th March 2013) - Kim, Ji‐Hyun; Yoon, Sujung; Won, Wang‐Youn; Lee, Chul; Lee, Chang‐Uk; Song, Kyo Young; Min, Jung‐Ah; Lyoo, In Kyoon; Kim, Tae‐Suk
Abstract Objective Improving and maintaining performance status is an important part of cancer treatment because it may predict patients' survival. Several cancer‐related medical conditions have been known to influence the functional performance of cancer patients. We here examined whether emotional distress would also contribute to performance decline of cancer patients. Methods With consecutive sampling, a total of 880 patients diagnosed as having cancer were recruited and evaluated on cancer‐related variables, emotional distress, and performance status using the standardized instruments. Results Approximately 8.9% of participants showed compromised performance rated 2 or more on the Eastern Cooperative Oncology Group performance status scale. Emotional distress was strongly associated with compromised performance after controlling for demographic and cancer‐related external risk factors. The effects of emotional distress on performance decline were likely to be remarkably greater in the younger age group (<45 years) than in old‐aged cancer patients (≥65 years). Conclusions Our results provide support for the independent effects of emotional distress on having a higher risk for performance decline in cancer patients. These effects seem to be age‐dependent suggesting that special clinical attention to emotional distress may be required in younger patients with cancer. Copyright © 2013 John Wiley & Sons, Ltd.